Epistemologia do testemunho : uma análise crítica à tese do reducionismo local - Silva, Ronaldo Miguel da (2016)
The topic of testimony has changed the course of epistemology in the last decades. It is commonly intuitive the true and rational belief based on testimony. However, there is a certain impasse in its approach to epistemology of testimony: a heated alternation in choosing philosophical sketches appear to be between sheer uncritical receptiveness on the one hand and intellectualist argumentation on the other – it is precisely here where the reductionist and anti-reductionist theses lie. Thus, given the importance of the epistemic status of testimony, this essay hinges over two objectives: i) to show the origin of the historical setting from which pervades contemporary discussions about the epistemology of testimony presenting the main theses vying for explaining the conditions where the testimonial belief may be regarded as the basic source of justification; ii) to consider in detail the idea of Rationality of Testimonial Rejection with which Elizabeth Fricker commits herself to, in order to present our thesis that this conception is demonstrably inconsistent not only by external forces, but also by forces of its own standards.